PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PADA PTS DI KALIMANTAN SELATAN - Rahmady Radiany (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
Goals of this research are; (1) to study and analyze significance influence of detail attention to service quality; (2) to study and analyze significance influence of orient result to service quality; (3) to study and analyze significance influence of orient people to service quality; (4) to study and analyze significance influence of orient team to service quality; (5) to study and analyze significance influence of organizational culture simultaneous to service quality. Sample in this research was taken by random sampling five Private Higher Education which major in management. The total sample are 100 students. Analysis technique used multiple linier regression .The research result indicates that: (1) there are significance influence of attention at detail representing the part of cultural variable to service quality to student by lecturer and employees; (2) there are significance influence of orient at result representing one of cultural variable to service quality to student by lecturer and employees; (3) there are significance influence of orient at one which who represent the cultural variable to service quality to student by lecturer and employees; (4) there are significance influence of orient at team which also represent the cultural variable to service quality to student by lecturer and employees; (5) there are significance influence of organizational culture simultaneous to service quality.